(untitled) (Proceedings of International Conference on Special Education, 2025)
Inclusive education, a cornerstone of modern educational philosophy, strives to create learning environments where all students can flourish academically and socially, regardless of their abilities or needs. However, despite its widespread recognition, implementing inclusive education programs poses substantial challenges for school administrators. Hence, this study evaluated school administrators’ challenges in implementing inclusive education and described their experiences managing these programs. Employing a qualitative design with a case study method, the research aimed to co-construct meaning with participants to understand their perspectives as leaders of inclusive schools. The findings highlighted that leadership vision and commitment, collaborative decision-making, and professional growth are critical factors influencing the success of inclusive education initiatives. These elements together serve as core pillars, forming a policy framework for inclusive education programs within educational institutions and impacting their efficacy and sustainability. Leadership vision and commitment ensure that inclusive practices are prioritized and integrated into the school’s culture. Collaborative decision-making fosters a shared responsibility among stakeholders, enhancing the implementation process and ensuring that diverse perspectives are considered. Professional growth opportunities enable educators to develop the necessary skills and knowledge to support all students effectively. The study describes a policy framework that promotes the essential roles of leadership vision, collaborative decision-making, and professional growth in supporting academic success in inclusive education environments. By focusing on evidence-based strategies, stakeholder engagement, and a commitment to quality, inclusive education can enhance academic achievements for all students.